Sintering and crystallisation of 45S5 Bioglass (R) powder - Bretcanu, Oana; Chatzistavrou, Xanthippi; Paraskevopoulos, Konstantinos; Conradt, Reinhard; Thompson, Ian; Boccaccini, Aldo R. (Journal of the European Ceramic Society, 2009)
The sintering process of 45S5 Bioglass® powder (mean particle size < 5 μm) was investigated by using different thermal analysis methods. Heating microscopy and conventional dilatometry techniques showed that bioactive glass sinters in two major steps: a short stage in the temperature range 500-600 °C and a longer stage in the range 850-1100 °C. The optimal sintering temperature and time were found to be 1050 °C and 140 min, respectively. Differential thermal analysis (DTA) showed that Bioglass® crystallises at temperatures between 600 and 750 °C. The characteristic crystalline phases were identified by Fourier Transformed Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM) and X-Ray Diffraction (XRD). The crystallisation kinetics was studied by DTA, using a non-isothermal method. The Kissinger plot for Bioglass® powder heated at different heating rates between 5 and 30 °C/min yielded an activation energy of 316 kJ/mol. The average value of Avrami parameter determined using the Augis-Bennett method was 0.95 ± 0.10, confirming a surface crystallisation mechanism. After sintering at 1050 °C for 140 min, the main crystalline phase was found to be Na2Ca2Si3O9. The results of this work are useful for the design of the sintering/crystallisation heat treatment of Bioglass® powder which is used for fabricating tissue engineering scaffolds with varying degree of bioactivity. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.sinter
Keywords: A. Sintering; B. Microstructure-final; Bioglass; C. Thermal properties; E. Structural applications